POTENSI 2-IP DAN TDZ PADA PERBANYAKAN TUNAS CABAI KATOKKON (CAPSICUM ANNUUM VAR. CHINENSE) SECARA IN VITRO - Ramlan, R; Sjahril, Rinaldi; Mantja, Katriani (Jurnal Galung Tropika, 2023)
Katokkon chili is a specific flora location in Toraja, South Sulawesi highlands that is unique compared to other types of chili peppers. Katokkon chili has a powerful and sharp distinctive aroma with a very high level of spiciness. Tissue culture could be a technique that is promising for breeding Katokkon. This study aims to determine the effect of using natural at a dose of potent 2-iP and synthetic TDZ growth regulators at various concentrations on the initiation of embryonic callus from callus explant. This research was conducted at the Laboratory of Plant Bioscience and Reproduction Biotechnology, Department of Agronomy, Faculty of Agriculture, Hasanuddin University, Makassar, in July-November 2022. This study was designed as an experiment it using a Completely Randomized Design (CRD) pattern with six treatments, each with three plicates. Callus was cultured on MS media with concentrations of 2-iP (1.0 mg L-1, 1.5 mg L-1, and 2.0 mg L-1) and TDZ (0.25 mg L-1, 0.5 mg L-1, and 1.0 mg L-1). The results showed that the administration of 2-iP and TDZ only formed roots and did not form buds. It gave 2-iP 1.0 mg L-1 formed roots on day 79 after plant culture with an average root length of 0.55 cm. The administration of TDZ 0.25 mg L-1 roots appeared on day 84 after pant culture with an average root length of 0.3 cm. A treatment of TDZ (1.0 mg L-1) and 2-iP (2.0 mg L-1) gave the best effect on callus weight Katokkon callus were compact in texture on administering 2-iP and TDZ. Callus changes color from white to green (embryogenic), and some experience browning.